Tari Matirto Suci Dewi Kandri dan Budaya Masyarakat Desa Kandri Kecamatan Gunungpati Kota Semarang : Kajian Korelasi Budaya (Jurnal Seni Tari, 2020)
The Matirto Suci Dewi Kandri dance was created by looking at the cultural background of the people in the village of Kandri which can be seen from the activities of the Kandri Village community namely religion, art, livelihoods, customs and cultural traditions that become the habits of the people of the village of Kandri so that some from the cultural embodiment of the Kandri Village community, it is seen in the Matirto Suci Dewi Kandri dance. This study aims to determine and describe cultural correlations with the Matirto Suci Dewi Kandri dance. Researchers used a qualitative descriptive method with an emic and ethical approach. Data collection techniques include observation, interview and documentation researchers use as a tool to obtain qualitative data. This research data analysis technique uses data reduction, data presentation and conclusion conclusions. The results showed that the cultural correlation of the Kandri Village through the Matirto Suci Dewi Kandri dance was formed through the Matirto Suci Dewi Kandri dance performance, namely (1) movement, in the Matirto Suci dance there were movements that were mbanyu mili and clever as the nature of the people of the gentle and hardworking Candri Village . (2) accompaniment, using a typical musical instrument from Kandri namely Kempling. (3) fashion, using a white cloth depicts holiness and simplicity. (4) the property, as a place to store holy water that is believed to be beneficial to everyone and (5) the stage, uses a red carpet that illustrates the struggle of the elders of the village of Kandri in damming the springs Keywords: Cultural Corellation, Matirto Suci Dewi Kandri Dance